Faktor yang Memengaruhi Personal Financial Planning pada Masyarakat Kota Kediri - Ningrum, Hafida Alviolita Dwi (Jurnal Ilmu Manajemen, 2021)
Personal financial planning is essential to have for everyone to achieve their financial goals. This research focuses on the people of Kediri City because BPS data shows that the per capita income of Kediri City is the highest compared to other cities in East Java Province. This research aimed to determine the effect of self-esteem, financial literacy, income, and digital financial services on personal financial planning. This research uses the causality research method and 193 respondents as the sample with cluster sampling obtained from online and offline questionnaires. Data were analyzed using multiple linear regression and processed with SPSS. This research shows results that self-esteem and financial literacy variables have a positive effect on personal financial planning. While the variables income and digital financial services did not affect personal financial planning. The results of the research are expected to be used by the Government of Kediri City in preparing education for its people to have better personal financial planning.